(3MGTjI Ydi efWb GdOhGfi (B( (3GdOhGdi (B)s - (3ejQ CHh GdaJMs; (3eMeO Hf YHO Gdedc GdOhGfj, CHh GdaJMs ((3Ydi GdHGfi s)
(3ChdgG (B:s
(3gh GdhUa HGdLejd GdN GdHGA EeG UdI ddhUa Ydi Cf jchf GdLejd s
(3BNQgG (B:s
(3hcTaJ Yf hLhg NQGFOg KbGH GdGMJLGH hYf cfhR aQGFOg JQGH GdGQJjGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdadSaI hGdefWbs